THE FORMATION MECHANISM OF COMMERCIALIZATION THE INTELLECTUAL PROPERTY OBJECTS: SECURITY KNOWLEDGE CONTEXTS OF MANAGEMENT ORGANIZATION - VIVCHAR, Oksana; MYKHAILYSHYN, Liliia; REDKVA, Oksana; SHATARSKYI, Artur (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In modern conditions of martial law, one the most important aspects of ensuring the effective functioning of business structures, as well as the formation of positive results its financial activity, is the existence of an effective security system for the commercialization of intellectual property objects, which will ensure business protection from threats. Protection is due to the ability of management bodies the business structures at the appropriate levels: to ensure sustainable economic development through the protection of intellectual property objects; to neutralize the negative impact of crisis phenomena on business structures; to form an adequate accounting system of financial flows and to strengthen the operational efficiency of control system in the process commercialization of intellectual property objects; ensure the implementation of work on the protection of the confidentiality of information constituting a commercial secret etc. Modern scientific research points to the fact that without a unified security system of business structures regarding the commercialization of intellectual property objects, it is impossible to find a way out of the crisis, stabilize the economic situation and create an effective mechanism for conducting business. The main components of the organizational and economic mechanism of commercialization of intellectual property objects at enterprises, which, in particular, include organizational processes; processes of technical and economic substantiation; processes of determining the market conformity of intellectual property objects to the needs of consumers; legal enforcement processes. Only the processes of determining the market suitability of intellectual property objects to the needs of consumers, that is, the processes of market research, are directly related to the process of commercialization. The other three components of the mechanism of commercialization of intellectual property objects are no less important, as they ensure the effective implementation of the actual process of commercialization or transfer. As the research results showed, the main influencing factors in the context of security science on the commercialization of intellectual property objects are: regulatory and legislative problem; the problem of valuation of intellectual property objects; personnel problem; the problem of organizational support for the commercialization of intellectual property objects. Therefore, the development of the organizational and economic mechanism of commercialization of intellectual property objects is a necessary and integral part of building a national innovation system aimed at increasing the competitiveness of the national economy and ensuring the transition to sustainable economic growth and strengthening of national security, including. Thus, the choice of the most acceptable method of commercialization should be justified from the point of view of the expected profit that it can bring to the owner of the rights in specific conditions.